Database Systems - Paul Beynon-Davies (New York Palgrave Macmillan, 2004)
Most modern-day organizations have a need to record data relevant to their everyday activities and many choose to organise and store some of this information in an electronic database. Database Systems provides an essential introduction to modern database technology and the development of database systems. This new edition has been fully updated to include new developments in the field, and features new chapters on: e-business, database development process, requirements for databases, and distributed processing. In addition, a wealth of new examples and exercises have been added to each chapter to make the book more practically useful to students, and full lecturer support will be available online.
Keywords: (ICE-2102) Application Development